Overview of the functional virulent genome of the coffee leaf rust pathogen Hemileia vastatrix with an emphasis on early stages of infection - Talhinhas, Pedro; Azinheira, Helena G.; Vieira, Bruno; Loureiro, Andreia; Tavares, Sílvia; Batista, Dora; Morin, Emmanuelle; Petitot, Anne-Sophie; Paulo, Octávio S.; Poulain, Julie; Da Silva, Corinne; Duplessis, Sébastien; et al. (Frontiers in Plant Science, 2014)
Hemileia vastatrix is the causal agent of coffee leaf rust, the most important disease of coffee (Coffea arabica). In this work, a 454-pyrosequencing transcriptome analysis of H. vastatrix germinating urediniospores (gU) and appressoria (Ap) was performed and compared to previously published in planta haustoria-rich (H) data. A total of 9234 transcripts were identified and annotated. Ca. 50% of these transcripts showed no significant homology to international databases. Only 784 sequences were shared by the three conditions, and 75% were exclusive of either gU (2146), Ap (1479) or H (3270). Relative transcript abundance and RT-qPCR analyses for a selection of genes indicated a particularly active metabolism, translational activity and production of new structures in the appressoria and intense signalling, transport, secretory activity and cellular multiplication in the germinating urediniospores, suggesting the onset of a plant-fungus dialogue as early as at the germ tube stage. Gene expression related to the production of carbohydrate-active enzymes and accumulation of glycerol in germinating urediniospores and appressoria suggests that combined lytic and physical mechanisms are involved in appressoria-mediated penetration. Besides contributing to the characterisation of molecular processes leading to appressoria-mediated infection by rust fungi, these results point towards the identification of new H. vastatrix candidate virulence factors, with 516 genes predicted to encode secreted proteins.